Clinical outcomes of pediatric kidney replacement therapy after childhood cancer: an ESPN/ERA registry study - Kaijansinkko, Henna; Bonthuis, Marjolein; Jahnukainen, Kirsi; Harambat, Jerome; Vidal, Enrico; Bakkaloglu, Sevcan A.; Inward, Carol; Sinha, Manish D.; Roperto, Rosa M.; Kuehni, Claudia E.; Biró, Erika; Kwon, Theresa; et al. (American journal of transplantation, 2025)
Cancer and its treatment may lead to kidney injury and the need for kidney replacement therapy (KRT). We identified 287 pediatric KRT patients with a history of malignancy from the European Society for Paediatric Nephrology/European Renal Association Registry. Of these, 197 had cancer as a primary cause of KRT (group 1) and 90 had a malignancy diagnosis before KRT (group 2). Two matched controls without malignancy were randomly selected for each patient. Data were complemented with a questionnaire. Median time to kidney transplantation (KT) from KRT initiation was 2.4 (IQR: 1.5-4.7), 1.5 (IQR: 0.4-3.3), 3.6 (IQR: 1.3 to Q3 not reached), and 1.1 (IQR: 0.3-3.6) years for group 1, their controls, group 2, and their controls, respectively. Overall 10-year mortality for those on KRT was higher among cancer patients vs controls in group 1: 16% vs 9% (adjusted hazard ratio 2.02, 95% CI: 1.21-3.37) and in group 2: 23% vs 14% (adjusted hazard ratio 2.32, 95% CI: 1.11-4.85). In contrast, 10-year patient survival after the first KT was comparable to controls (93% vs 96%; 100% vs 94%, in groups 1 and 2, respectively). In summary, childhood cancer survivors’ KT was delayed, and their overall mortality when on KRT was increased, but once transplanted, their long-term outcome was similar to other KT recipients.
Online verfügbar 7 November 2024, Version des Artikels 3 April 2025
Gesehen am 14.10.2025